Psoriasiform Dermatitis: From Pathogenesis to New Therapeutic Opportunities - Eugenia Veronica Di Brizzi; Stefano Caccavale; Caterina Mariarosaria Giorgio; Giuseppe Argenziano; Anna Balato (Life)
Psoriasiform dermatitis refers to a spectrum of inflammatory skin disorders that resemble psoriasis both clinically and histologically. These conditions can occur idiopathically or as paradoxical reactions to biologic or targeted therapies, particularly in patients with atopic or autoimmune backgrounds. Histologic features often include acanthosis, parakeratosis, and lymphocytic infiltrates, but without the full molecular signature of classical psoriasis. This review provides an overview of psoriasiform dermatitis with a focus on its clinical presentation, differential diagnosis, and the immune pathways involved. Drug-induced forms, especially those triggered by anti-TNF agents, IL-4/IL-13 blockers, and JAK inhibitors, are highlighted due to their growing clinical relevance. We also summarize the main topical and systemic treatments, including corticosteroids, calcineurin inhibitors, PDE4 inhibitors, and JAK-STAT- or IL-23-targeted therapies. A better understanding of psoriasiform dermatitis is crucial to improve diagnosis and to guide treatment, especially in complex or refractory cases.